Effect of switching from conventional continuous subcutaneous insulin infusion to sensor augmented pump therapy on glycemic profile in Japanese patients with type 1 diabetes - Matsuoka, Atsuko (Diabetol Int, 2018)
AIMS: Evidence suggests that sensor augmented pump (SAP) therapy is superior to conventional continuous subcutaneous insulin infusion (CSII) for achieving glycemic control in patients with type 1 diabetes. However, the clinical benefit of SAP therapy in East Asians has not yet been demonstrated. METHODS: The effect of switching from conventional CSII to SAP therapy on glycemic profile was examined in 18 Japanese patients with type 1 diabetes. The glycemic profile of the patients was determined by retrospective continuous glucose monitoring (CGM) within 1 month before the treatment switch, whereas that at 6 and 12 months after the switch was evaluated with the CGM function of the SAP device. Hemoglobin A1c levels were also measured before and after the switch to SAP therapy. RESULTS: The duration of hypoglycemia was significantly decreased at both 6 and 12 months after the change in treatment (6.6 ± 4.5, 3.2 ± 4.1, and 3.0 ± 2.8 min/h for before and 6 and 12 months, respectively), as was the HbA1c level at 12 months (7.8 ± 1.0 and 7.4 ± 0.9%, respectively). The duration of hyperglycemia did not differ between before and after the treatment switch. The decline in HbA1c level at 12 months after the switch to SAP was negatively correlated with age. CONCLUSION: Switching from conventional CSII to SAP therapy was associated with a decrease in both the duration of hypoglycemia and the level of HbA1c in Japanese patients with type 1 diabetes.